Voluntary salt intake by feedlot steers - L.H. Harbers; L.C. Warren (Kansas Agricultural Experiment Station Research Reports, 1971)
Because it is a standard practice, adding salt to livestock rations has not received much attention in the past several years. Salt is universally added at 0.5% of the diet, but studies here in the early 50's showed salt needs of cattle are related to dietary roughage levels.
Keywords: Cattlemen& #x27; s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Salt intake; Feedlot steers